Experimental Measurement of Rifle Dynamics During the Range Shooting of Biathlon Weapons. (2015) - Koptyug, Andrey; Ainegren, Mats
Abstract: Some of the shooting training that biathletes implements takes place indoors, even in hotel rooms or at home, through so-called "dry firing" training. It involves imitating shooting at a target with real rifle but without ammunition, when the result is evaluated by various electronic devices counting the number of virtual hits. But dry firing cannot adequately represent real shooting, as it does not produce any rifle recoil, which significantly limits its value for the training. To reach a higher realism of the dry firing training a system mimicking the weapon recoil is therefore needed. Present research aims to overcome an existing lack of data on the dynamics of small caliber rifles recoil dynamics. Present paper describes first measurement results acquired in the controlled environment of the shooting range. Two types of experiments were carried out with firing freely suspended rifle and when backed with the force measurement device (load cell). Average recoil peak force values were reaching 5 kg, rising from zero for about 10-15 ms and keeping altogether for about 30-40 ms. Corresponding energy going into the recoil motion of the rifle is found to be about 390 J. The measured values provide an adequate input for designing the devices mimicking the biathlon weapon recoil in dry firing training.